Introducing the Methodology of ‘Critical Fashion Practice’ into Fashion Design Studies in Croatia - Katarina Nina Simončič (Tekstilec, 2023)
Since the advent of mass production, where the quantity of clothing reflects the consumption habits of society, fashion has become a reflection of the capitalist atmosphere. The reciprocity of society and fashion begin to occupy and initiate all the intense theoretical discussions that lead to the emergence of new branches of scientific research in the social-humanist field. The two most important scientific field are the history of fashion and fashion theory, whose analyses focus on the role of clothing as part of material culture conditioned by the political, social, economic and religious context. These two branches of science are increasingly becoming the focus of fashion design students in the education system. As a result, the above disciplines are included as separate compulsory subjects in the fashion design programme, developing strong theoretical skills at the expense of practical production and collection making. This approach represents a significant departure from the curricula of previous fashion design programmes, where the conditioning of the profession by political, economic, technological and social impulses was evident. In 2014, the former Centre for Fashion Studies at the Stockholm College highlighted the problem of a strong dichotomy between theoretical and fashion design courses in fashion design programmes and organised a symposium entitled ‘Fashion Issues: Critical Fashion Studies’. Based on his guidelines, the project ‘Critical Fashion: Reflections in Theory and Practice’ was developed as part of the degree programme at Beckmans College of Design in Stockholm, resulting in a highly discursive internet platform with the symbolic name ‘Critical fashion practice’. The aim of the new approaches was to rethink the importance of theoretical approaches in observing fashion production based on reflection of social relations, media images and personal experiences. This paper analyses the contribution of the platform ‘Critical fashion practice’ in the context of theoretical-practical teaching for fashion design students at the Faculty of Textile Technology, University of Zagreb.